Effectiveness of Apuwood Plants (Pistia Stratiotes) Using the Phytoremediation Method in Reducing Bod Levels in Ciprat Langitan Magetan Batik Waste - Febrianti, Rizqi Isna; Wibowo, Pipid Ari; Marsanti, Avicena Sakufa (Syntax Corporation Indonesia, 2024)
The batik industry generally consists of residue, residual dye water, residual wax and batik pelorodan water. The characteristics of batik liquid waste include high levels of Biological Oxygen Demand, Chemical Oxygen Demand, and Total Suspended Solids. Batik industry waste is considered dangerous, because its characteristics can pollute waters such as turbidity in river water. The aim of this research is todetermine the effectiveness of using apu wood plants (Pistia Stratiotes) in reducing the BOD value in Ciprat Langitan Simbatan Magetan batik waste.The method used in this research is experimental, with analysis using Quasi Experimental and using a Pretest-posttest Control Group Design.The results of measuring BOD levels with phytoremediation treatment of apu wood plants on the 3rd day were 114 mg/l, on the 6th day it was 71 mg/l and on the 9th day it was 53 mg/l. The percentage of effectiveness in reducing BOD levels on day 3 was 9.78%, on day 6 it was 45.31% and on the last day it was 58.20%. There was a reduction in BOD levels with phytoremediation using apu wood plants. The effectiveness of the apu wood plant in reducing BOD levels was found with an exposure time of 9 days. Apart from that, a long-standing treatment of more than 9 days can be used to measure the effectiveness of apu wood plants in reducing the BOD levels of batik liquid waste.